2017
DOI: 10.22436/jnsa.010.04.55
|View full text |Cite
|
Sign up to set email alerts
|

Generalizations of Hu-type inequalities and their applications

Abstract: In this paper, we present some new generalizations of Hu-type inequalities, and then we obtain some new generalizations and refinements of Hölder's inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In FS theory, t-conorm (T * ) and t-norm (T) are very important to the generalization of intersection or union of fuzzy sets [34,42,46,[55][56][57][58][59][60][61].…”
Section: Hamacher T-norm and Hamacher T-conormmentioning
confidence: 99%
“…In FS theory, t-conorm (T * ) and t-norm (T) are very important to the generalization of intersection or union of fuzzy sets [34,42,46,[55][56][57][58][59][60][61].…”
Section: Hamacher T-norm and Hamacher T-conormmentioning
confidence: 99%
“…Zhao et al [ 14 ] found that the Hölder inequality for the pan-integral holds if the monotone measurer is subadditive. Tian [ 15 18 ] gave some new properties and refinements of the Hölder and reverse Hölder inequalities. For more detail, the reader may consult [ 19 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Steele et al [5] employed the Hölder inequality to place lower bounds on the sum of and 1.0 running masses. Tian et al [6][7][8][9][10][11][12][13] gave some new properties, generalizations, refinements, and applications of Hölder's inequalities. Wu [14,15] presented some new sharpened and generalized versions of Hölder's inequalities in classical real analysis.…”
Section: Introductionmentioning
confidence: 99%